266 NON-HIGH-DENSITY LIPOPROTEIN CHOLESTEROL IN THE METABOLIC SYNDROME. (1st January 2006) - Huang, J.; Parish, R.; Yu, H.; Bass, P. F.; Mansi, I.; Kennen, E.; Davis, T.; Carden, D.
Abstract : Background: The metabolic syndrome (MS) refers to a cluster of risk factors, including central obesity, elevated BP, insulin resistance, and dyslipidemia (DLP) characterized by elevated triglycerides (TG) and low high-density lipoprotein cholesterol (HDL). MS currently affects 27% of US adults and is associated with increased cardiovascular morbidity and mortality. Aggressive lowering of low-density lipoprotein cholesterol (LDL) is critical in coronary artery disease (CAD) prevention. However, when TG levels are high, as often seen in MS, LDL value cannot be calculated. Non-HDL cholesterol (total cholesterol (TC) - HDL) is a measure of all apo-B containing lipoproteins with high atherogenic potential and is considered as a secondary target for lipid therapy in patients with high TG or MS. The purpose of this study was to determine the association between MS and TC, LDL, and non-HDL. Methods: Diagnosis of MS was based on NCEP criteria among 928 outpatients in a public hospital. t-Test was used for comparison of lipid components between those with and without MS. Results: Seventy percent of patients were black, 68% female; 53% had MS. Among MS patients, 87% had TG > 150 (mg/dL); 85% low HDL; 63% TC > 200; 64% LDL > 100; 69% non-HDL > 130. The results of statistical analysis are as follows: Conclusions: The prevalence of MS is high in this patient population. The prevalence of DLP is high in patients with MS. Besides TG and HDL, only non-HDL, but not TC or LDL, is significantly associated with MS. These results suggest that use of non-HDL as the therapeutic target for lipid management is appropriate in MS patients when LDL is not calculable.